Revival of agricultural cooperatives in Uganda - Kwapong, Nana Afranaa; Korugyendo, Patrick Lubega (International Food Policy Research Institute, 2010)
Due to their highly democratic and locally autonomous nature, cooperatives have a potentially strong role in reducing poverty and social exclusion, and promoting rural and national development (Develtere et al. 2008; Birchall 2004, 2003). However, the development of cooperatives has been limited by inadequate research. There is a dearth of up to date literature on the status of African cooperatives since the liberalization of the agriculture sector in the mid-1990s (Wanyama et al. 2008). In addition, policymakers, practitioners, and others harbor outdated views on cooperatives, hampering progress in the sector. Cooperatives in Uganda, especially those involved in cash crops, successfully provided agricultural-related services to farmers until the mid-1980s. At that time, due to political instability, liberalization of markets, and mismanagement, among other reasons, almost all the cooperatives failed. However, a few survived, and cooperatives are enjoying a revival in Uganda. This policy note is based on a case study of the recent revival and reform of the agricultural cooperative sector in Uganda.